(untitled) (Revista Brasileira Multidisciplinar, 2026)
Care-Educational Technologies favour the protagonism and autonomy of parents and family members in caring for children’s health. The aim of this study is to identify and characterise the trends in theses and dissertations produced in Brazil on care-educational technologies used in educational activities for parents and family members of children in Primary Health Care. This is a narrative bibliographical review carried out in the Theses and Dissertations catalogue of the Coordination for the Improvement of Personnel. The research took place in the first half of June 2024. The study had no time frame. The inclusion criteria were theses and dissertations that presented care-educational technologies for the health education of parents and family members of children aged 0 to 5 in the context of primary care. Productions that were developed in the hospital context and aimed at continuing education were excluded. The care-educational technologies presented in the studies were: booklet, booklet, serialised album, video and website. The review showed that the care-educational technologies presented were developed to meet a specific child health need. Thus, there is a gap with regard to technologies for promoting children’s health in a broader context, which enhance knowledge about growth and development, the importance of affection and children’s rights.